Democratizing Code: How GPT and Large Language Models Are Reshaping the Landscape of Software Creation - Prakash Raj Ojha (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article examines the transformative impact of Generative Pre-trained Transformers (GPT) and Large Language Models (LLMs) on software development practices. Through a comprehensive analysis of current literature and industry applications, we investigate how these AI-driven technologies are revolutionizing code generation, debugging, and overall development workflows. Our findings indicate that GPT and LLMs significantly enhance programmer productivity by automating routine tasks, providing real-time code suggestions, and facilitating rapid prototyping. Moreover, these models demonstrate potential in democratizing software development by lowering entry barriers for non-experts. However, the integration of AI in development processes also raises important ethical considerations and challenges, including potential biases in code generation and the changing nature of programming skills. This research contributes to the growing body of knowledge on AI-assisted software engineering and provides insights into the future trajectory of the field, suggesting that the symbiosis between human developers and AI models will likely define the next era of software development.